Prolonged treatment of refractory Wegener's granulomatosis with 15-deoxyspergualin: an open study in seven patients - Schmitt, Wilhelm; Birck, Rainer; Heinzel, Peter A.; Göbel, Ursula; Choi, Mira; Warnatz, Klaus; Peter, Hans H.; Woude, Fokko J. van der (Nephrology, dialysis, transplantation, 2005)
BACKGROUND: A subset of patients with Wegener's granulomatosis does not respond to daily oral cyclophosphamide (CYC) plus corticosteroids or suffers from intolerable side effects. A 6 month course of the immunosuppressant 15-deoxyspergualin (DSG) has previously been employed successfully in these refractory cases. However, there are no reports on long-term treatment with DSG. METHODS: To document the effects of prolonged DSG treatment, this study reports on seven patients suffering refractory Wegener's granulomatosis, who were successfully treated with DSG over an average of 26.5 months (range: 11-55.5 months). RESULTS: Before administration of DSG, patients had experienced an average of 6.6 relapses (range: 3-12) under an average of 5.4 (range: 2-11) different therapeutic approaches, which included CYC in all cases. All suffered active disease when DSG was initiated. Four were unresponsive to CYC and three did not tolerate it. DSG (0.5 mg/kg/day subcutaneous) was given for 2-3 weeks until the leukocyte count dropped to 3000/microl, followed by a rest until a leukocyte count of 4000/microl was reached again. No other immunosuppressants besides corticosteroids were given. All patients showed a long-lasting, favourable response to DSG with complete (n = 5) or partial (n = 2) remission. Only one case relapsed while being treated with DSG. Termination/interruption of DSG was followed by relapse in four of five occasions. Resumption of DSG led to complete remission. Currently, five of the seven patients are still treated with DSG and are in remission. Infections, mainly of the respiratory tract, were observed in five cases and resolved after treatment. One case developed a third-degree heart block that required pacing. CONCLUSIONS: In patients with refractory Wegener's granulomatosis, prolonged treatment with DSG seems safe and successful.
Gesehen am 25.05.2022